Optimal coordinating gearshift control of a two-speed transmission for battery electric vehicles. (February 2020) - Tian, Yang; Yang, Haitao; Mo, Wenwei; Zhou, Shilei; Zhang, Nong; Walker, Paul D.
Highlights: Development of a seamless two-speed transmission applied in a BEV. Proposing a power-on gearshift control strategy. Improving the gearshift quality by the optimal coordinating gearshift controllers. Developing observers for estimating the unmeasured torque information to achieve the feedback control. Abstract: With the sustained technology advancement in the power battery, battery electric vehicles (BEVs) are considered as the most advisable alternatives of their internal combustion engine (ICE) counterparts. Research reveals that the implementation of multispeed transmissions for BEVs can reduce the vehicle energy consumption, improve the vehicle dynamic performance and downsize the battery package and the driving motor volume. Considering the potential advantages of multispeed transmissions equipped BEVs, this paper presents an investigation into the optimal coordinating gearshift control of a seamless two-speed transmission for BEVs. Firstly, to achieve the gearshift transient behaviour, the mathematical model of the powertrain system is established. Next, model-based gearshift tactics are proposed for the torque phase and the inertia phase respectively. Subsequently, the proposed control tactics based optimal controllers are developed to achieve high-quality gearshift in the whole gear shifting process. To be more specific, in the torque phase, the controller aims at optimising dual objectives together, namely the vehicle jerk and friction work, and the control objective of the inertia phase only focuses on decreasing the friction work due to the coordinating gear shifting tactic. Finally, based on available sensor signals, sliding mode observers are employed to estimate unmeasurable torque as feedback information for the optimal controllers in different gear states. Simulation results demonstrate that the devised control approaches can promote gear change performance comprehensively.